Maximizing Operational Efficiency: Utilizing Blockchain for Comprehensive Tracking and Visibility throughout the Supply Chain - Shankaran, Sabareesan (International Journal of Supply Chain and Logistics, 2024)
Purpose: The purpose of this research is to explore the transformative potential of blockchain technology in supply chain management, focusing on its ability to address inefficiencies, enhance transparency, and reduce fraud. It aims to evaluate blockchain's role in enabling end-to-end supply chain tracking through decentralization, immutability, and real-time data sharing while assessing its integration with IoT and AI to provide predictive, data-driven decision-making. The study also seeks to identify challenges such as scalability, regulatory constraints, and cultural barriers and propose solutions like Layer 2 technologies and industry collaboration to facilitate ethical and sustainable practices and advance international trade. Methodology: The study examines blockchain technology's decentralization, immutability, and real-time data-sharing in supply chain management. It uses case studies, such as Walmart's food traceability initiative, to demonstrate practical applications, showing time reductions from six days to seconds. The research explores integrating IoT and AI to improve data capabilities for better decision-making and addresses challenges like scalability and regulatory barriers. Proposed solutions include Layer 2 technologies and fostering industry collaboration. This mixed-method approach combines qualitative insights with technological analysis of blockchain in the supply chain. Findings: Blockchain reduces fraud by 50% and boosts operational efficiency by 30%. Case studies reveal significant improvements in traceability, e.g., reducing traceability time from six days to seconds. Blockchain enhances predictive capabilities and decision-making when combined with IoT and AI. Challenges include scalability, regulatory barriers, and resistance within organizational cultures. Solutions such as Layer 2 technologies, improved anonymity measures, and industry cooperation are essential for overcoming barriers. Unique Contributions to Theory, Policy, and Practice: Blockchain is a transformative technology in supply chain management, offering decentralization, immutability, and real-time data sharing. It reduces fraud by 50% and boosts operational efficiency by 30%. The integration of blockchain with IoT and AI enhances predictive analytics and decision-making, paving the way for future research on technology convergence. Regulatory frameworks are needed to tackle scalability, resistance, and anonymity issues for smoother adoption. Industry cooperation is crucial to overcome barriers, and policies should enforce ethical, transparent supply chain practices. Case studies, like Walmart’s food traceability, show significant improvements, with traceability times reducing from six days to seconds. Businesses are encouraged to use Layer 2 technologies for better scalability and efficiency. Overall, blockchain holds promise for sustainable practices and the evolution of international trade.